Modernization of the Justice Sector in Algeria: Study in Achievements and Diagnosis of Obstacles - Adoudi, Moufid (Milev Journal of Research and Studies, 2021)
The sector of justice defined several reform in order to develep them and retionalize it various serrices where the media and modern communication Play important role in dealing with the media communication and services on both the physical and temporal, something that breaks into the administration from the paper administration the modern digital management that save lot of effort and money and inorder to improve and rationalize administrative services in the sector of justice, the Algerian government includes a set of reforms supported by a legal and legislative framwork that guarantees good for it to continue and overcome its obstacles.For the purpose of discussing this research we relied on the descriptive approach.